2008
DOI: 10.1007/s10800-008-9505-7
|View full text |Cite
|
Sign up to set email alerts
|

Thin-film composite nanofiltration membranes prepared by electropolymerization

Abstract: A novel approach to preparation of composite asymmetric nanofiltration membranes is reported based on a thin selective layer deposited by electropolymerization (EP) on top of an asymmetrically porous and electronically conductive porous support. Support films with ultrafiltration characteristics were cast from a concentrated dispersion of carbon black particles, a few tens of nanometers large, in a solution of polysulfone followed by precipitation in a non-solvent bath (phase inversion). Composite membranes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…A similar trend was described by Benson et al (2013) who electropolymerized PANI on CNTs in a hydrochloric acid medium and reported that higher current densities increased PANI thickness and decreased surface porosity . Furthermore, Gloukhovski et al were able to fabricate dense nanofiltration membranes by electropolymerizing a PANI coating on an electrically conductive support layer at high current densities (3.78 mA cm –2 ) …”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…A similar trend was described by Benson et al (2013) who electropolymerized PANI on CNTs in a hydrochloric acid medium and reported that higher current densities increased PANI thickness and decreased surface porosity . Furthermore, Gloukhovski et al were able to fabricate dense nanofiltration membranes by electropolymerizing a PANI coating on an electrically conductive support layer at high current densities (3.78 mA cm –2 ) …”
Section: Resultssupporting
confidence: 76%
“…48 Furthermore, Gloukhovski et al were able to fabricate dense nanofiltration membranes by electropolymerizing a PANI coating on an electrically conductive support layer at high current densities (3.78 mA cm −2 ). 46 3.1.3. Membrane Rejection Properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrically conducting form of PANI is emeraldine, which is obtained through the electrochemical polymerization of PANI under acidic condition ( Figure 10 ) [ 32 , 129 , 130 , 131 , 132 ].…”
Section: Membrane Foulingmentioning
confidence: 99%
“…Conducting polymer as molecular wires is an excellent choice because of their long p-conjugation length as well as their high metal conductivity [1]. In recent years, polymer-polyaniline (PANI) conductive polymeric composites have received considerable attention because of their potential applications in electrodes, biosensors, batteries, antistatic coatings, gas sensors, membranes and light emitting diodes [2][3][4][5][6][7][8][9][10][11][12][13][14] PANI is a conducting polymer [15] which has been extensively studied due to its relatively high conductivity and potential application in electronic devices. The general formula for ideal PANI materials in their base forms consists in three (-C 6 H 4 -NH-) benzenoid units and one (-N=C 6 H 4 =N-) quinoid unit [16].…”
Section: Introductionmentioning
confidence: 99%